HIGH SCHOOL EFL TEACHERS’ PRACTICE OF AUTHENTIC SPEAKING ASSESSMENT AT NISSA SCHOOL - Suwarni, Gizi Sri (Universitas Muhammadiyah Prof. DR. HAMKA, 2023)
This study investigates the implementation of authentic Speaking Skill assessment at Nissa High School in Bekasi, West Java. The research delineates authentic assessment practices, including those for authentic speaking assessments, measurement techniques, challenges encountered during assessment, and strategies employed to overcome these challenges. The narrative also highlights the proactive efforts undertaken by the teacher. Employing a descriptive research design with a qualitative approach and interviews for data collection, this research involves three English teachers from Nissa High School as participants. The research results show that high school teachers carried out authentic assessments of speaking skills well. However, its implementation cannot be said to be optimal because of the modifications in the curriculum transition from the 2013 Curriculum to the